2018
DOI: 10.1001/jama.2018.16504
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion With 1-Year Mortality Among Patients With End-Stage Renal Disease

Abstract: IMPORTANCE The Affordable Care Act Medicaid expansion may be associated with reduced mortality, but evidence to date is limited. Patients with end-stage renal disease (ESRD) are a high-risk group that may be particularly affected by Medicaid expansion. OBJECTIVE To examine the association of Medicaid expansion with 1-year mortality among nonelderly patients with ESRD initiating dialysis. DESIGN, SETTING, AND PARTICIPANTS Difference-in-differences analysis of nonelderly patients initiating dialysis in Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 22 publications
3
102
0
Order By: Relevance
“…Such early changes in outcomes have also been also reported in other analyses of expansion in insurance coverage. 5,7 However, these prior analyses were either focused on a single state (Massachusetts) or a specific chronic disease population (end-stage renal disease). The only randomized clinical trial of Medicaid expansion to date (the Oregon Health Study 6 ) did not demonstrate significant improve- ments in cardiovascular risk factors, such as hypertension or hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such early changes in outcomes have also been also reported in other analyses of expansion in insurance coverage. 5,7 However, these prior analyses were either focused on a single state (Massachusetts) or a specific chronic disease population (end-stage renal disease). The only randomized clinical trial of Medicaid expansion to date (the Oregon Health Study 6 ) did not demonstrate significant improve- ments in cardiovascular risk factors, such as hypertension or hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…6 In a recent analysis of patients with end-stage renal disease, Medicaid expansion was associated with lower allcause mortality. 7 Cardiovascular disease and its risk factors disproportionately affect individuals of lower socioeconomic status and those who are uninsured. 8,9 Since Medicaid expansion has been associated with improvements in the management of diabetes, 10 increased use of cardioprotective medications, 11 and access to preventive care, 12 expansion in health insurance coverage may have a potential association with cardiovascular disease and mortality.…”
mentioning
confidence: 99%
“…Secondary outcomes were insurance status at dialysis initiation, the presence of AV fistula or graft at initiation (limited to hemodialysis patients), and receipt of predialysis nephrology care. 1,7 Covariates included age, sex, primary cause of kidney failure (diabetes, hypertension, and other), comorbid conditions, current smoking, alcohol dependence, hemoglobin level, serum albumin level, body mass index, and year. We used multiple imputation for missing data; <12% of values were missing for covariates except for albumin level (29%).…”
Section: Trends In Mortality Among Patients Initiating Maintenance DImentioning
confidence: 99%
“…Another angle to examining mortality is to measure changes among more targeted populations gaining coverage. Two published studies have found significant mortality reductions due to the ACA-one examining the Medicaid expansion's effects among high risk patients starting dialysis (Swaminathan et al, 2018), and the other finding reduced disease-related mortality among young adults gaining coverage under the dependent coverage provision (McClellan, 2017). This is an impressive literature, but holes remain.…”
Section: Effects Of the Aca On Health Care Utilization And Healthmentioning
confidence: 99%